2020
DOI: 10.1021/acsmedchemlett.9b00679
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Gene Signature for Pyrazolopyrimidine Derivative c-Src Inhibitor 10a Sensitivity in Melanoma Cells

Abstract: Melanoma is a highly aggressive cancer with poor prognosis. Although more than 80% of melanomas harbor an activating mutation in genes within the MAPK pathway, which are mutually exclusive, usefulness of therapies targeting MAPK pathway are impeded by innate and/or acquired resistance in most patients. In this study, using melanoma cells, we report the efficacy of a recently developed pyrazolo [3,4-d]pyrimidine derived c-Src inhibitor 10a and identify a molecular signature which is predictive of 10a chemosensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In glioblastoma, NSUN2 is a target gene of nuclear respiratory factor 1 (NRF1), and its high expression is associated with resistance to temozolomide (TMZ) therapy [64]. In melanoma, the increased expression of NSUN5 is used to predict the sensitivity of melanoma cells to the pyrazopyrimidine derivative c-Src inhibitor 10a [159].…”
Section: Rna Methyltransferases In Cancer Therapymentioning
confidence: 99%
“…In glioblastoma, NSUN2 is a target gene of nuclear respiratory factor 1 (NRF1), and its high expression is associated with resistance to temozolomide (TMZ) therapy [64]. In melanoma, the increased expression of NSUN5 is used to predict the sensitivity of melanoma cells to the pyrazopyrimidine derivative c-Src inhibitor 10a [159].…”
Section: Rna Methyltransferases In Cancer Therapymentioning
confidence: 99%
“…Baris et al reported pyrazolopyrimidine derivative 39 (Figure 6) and showed that it was a potent inhibitor (IC 50 = 0.09–9.01µM) of 15 melanoma cells. [ 62 ] The variation in inhibitory activity suggests various underlying mechanisms of action on melanoma cells. Therefore, the gene signature of chemo‐selectivity for compound 39 was identified.…”
Section: Anticancer/antiproliferative Activitymentioning
confidence: 99%